Association between oxidative balance score and female infertility from the national health and nutrition examination survey 2013–2018 - Su, Zhe; Ding, Peihui; Su, Wenjing; Li, Xia; Li, Yiqian; Li, Xiaoran; Lao, Kaixue; Wang, Yanlin (Frontiers in Endocrinology, 2024)
The correlation between oxidative stress and female infertility pathogenesis was established, and the oxidative balance score (OBS) can serve as a measure of overall oxidative stress burden within an individual. Prior reports have not addressed the relationship between OBS and female infertility. This study endeavors to investigate the association between infertility risk in female and OBS.The analysis focused on data from the National Health and Nutrition Examination Survey 2013-2018. OBS was determined from 16 dietary components and 4 lifestyle components.Multivariate logistic regression was employed to investigate the relationship between OBS and female infertility. Further stratified analysis was conducted to examine the associations across various subgroups. To elucidate the dose-response relationship between infertility risk in female and OBS, a restricted cubic spline function was employed.The study included a total of 1410 participants. Through weighted multivariable logistic regression analysis, we observed a consistent inverse correlation between OBS and the risk of female infertility [OR (95% CI) = 0.97 (0.95, 0.99), p = 0.047]. When participants were segregated into quartiles based on OBS, those in the highest quartile had a 61% [OR (95% CI) = 0.39 (0.2, 0.79), p = 0.01] reduced risk of infertility compared to those in the lowest quartile of OBS. A trend test assessing OBS by quartile also revealed the relationship between OBS and female infertility. This correlation remained constant across both dietary and lifestyle OBS.Additionally, lifestyle OBS and female infertility exhibited a nonlinear association. A sensitivity analysis verified the consistency of our findings.The study found that a higher OBS is associated with a lower prevalence of female infertility. These results emphasized the potential role of oxidative homeostasis in the pathogenesis of infertility and highlighted the importance of follow-up studies and prevention strategies.